أهمية الذكاءات المتعددة في تعليم مهارة التحدث باللغة العربية للطلاب غير الناطقين بها: Importance of multiple intelligences in teaching Arabic speaking skills to non-native students - Bendary, Sahar Abedelrahman Muhammad; Siti Salwa binti Mohd Noor, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث في سياق تعليم اللغة العربية بصفة عامة لغير الناطقين بها، أكدت العديد من الدراسات على أهمية مراعاة قدرات المتعلمين والفروق الفردية بينهم، الأمر الذي يستوجب من المعلم إدراك هذه الفروق أثناء التدريس، وعمل مواءمة بينها وبين أساليب وإستراتيجيات التدريس المستخدمة، وذلك للوصول بالطلاب إلى الحد الأمثل في الأداء. تهدف هذه الدراسة إلى توظيف الذكاء اللغوي في تحسين مهارة التحدث لدى طلاب الصف الثامن غير الناطقين باللغة العربية، وقد اعتمدت الدراسة على الاختبارين القبلي والبعدي مستخدمة عينة مكونة من 45 طالبا، 23 منهم عينة تجريبية درست محتوى التعلم باستخدام إستراتيجيات الذكاء اللغوي، و22 عينة ضابطة درست المحتوى التعليمي بالطريقة التقليدية. أظهرت النتائج ارتفاع مستوى تحصيل طلاب المجموعة التجريبية، ويعزى ذلك التحسن إلى استخدام إستراتيجيات الذكاء اللغوي في عملية التدريس. حيث أظهرت النتائج المتعلقة بالاختبار البعدي ارتفاع الوسط الحسابي لطلاب المجموعة التجريبية مقارنة بالمجموعة الضابطة، بواقع (49.11) و(32.84) على التوالي، ويمكن أن تعزى هذه النتيجة إلى توظيف إستراتيجية الذكاء اللغوي، إحدى أهم أنواع الذكاءات المتعددة، بالإضافة إلى أن البرنامج المعد وفق الذكاء اللغوي قد وظف بعض الأساليب العملية مثل العصف الذهني، والتعلم التعاوني، وطرح ومناقشة الأسئلة، والاستنتاج، وممارسة بعض مهارات التحدث، مثل الاستجابة للأسئلة كلاميًّا (التحدث)، والتعبير عن حكاية مصورة، وتكوين جمل سهلة سليمة التركيب. ومن هنا تتبين أهمية فكرة توظيف إستراتيجيات الذكاءات المتعددة، في تعليم مهارات اللغة العربية للطلاب غير الناطقين بها، وخاصة مهارة التحدث. ABSTRACT In the context of teaching Arabic to non-native speakers in general, many studies have emphasized the importance of taking into account learners' abilities and individual differences, that which requires the teacher to be aware of these differences during teaching and to harmonize them with the teaching methods and strategies used, in order to bring students to the optimal level of performance. This study aims to employ linguistic intelligence to improve the speaking skills of eighth-grade students who are non-native speakers of Arabic. The study relied on pre- and post-tests using a sample of 45 students, 23 of whom were an experimental sample that studied the learning content using linguistic intelligence strategies, and 22 were a control sample that studied the educational content using the traditional method. The results shows an increase in the level of knowledge acquisition of the students in the experimental group, and this improvement is attributed to the use of linguistic intelligence strategies in the teaching process. The results of the post-test shows a higher arithmetic mean for the experimental group students compared to the control group, by (49.11) and (32.84) respectively. This result can be attributed to the use of the linguistic intelligence strategy, one of the most important types of multiple intelligences. In addition, the program prepared according to linguistic intelligence employed some practical methods such as brainstorming, cooperative learning, asking and discussing questions, inference, and practicing some speaking skills, such as responding to questions verbally (speaking), expressing a picture story, and forming easy, well-structured sentences. Hence, the importance of the idea of ​​employing multiple intelligence strategies in teaching Arabic language skills to non-native students, especially speaking skills, becomes clear.